Unilateral Molar Distalization With Molar Slider (Two Case Report) - Ahmet Keleş; Bükem İşgüden (Galenos Yayinevi, 1999)
We selected 2 patients for unilateral molar distalization. Dentally, the patients presented unilateral Class II molar relationship. The patients were on permanent dentition; second molars were erupted and presented well-aligned lower dental arch. For maxillary molar distalization a new intraoral appliance was developed. Molar Slider was composed of 2 premolar and 2 molar bands and the anchorage unit was composed of a Nance button with anterior bite plane. In its design from the palatal side, the point of distal force application was carried towards the level of center of resistance of the maxillary 1st molar. Ni-Ti coil spring was used and 200g of distal force was applied to the Class II 1st molar. Lateral cephalograms were taken and analyzed before and 2 months after the molar distalization. The results showed that Class II molars distalized bodily no mesial migration of Class II 1st premolars were observed, incisor protrusion and incisor proclination was observed after the removal of Molar Slider. Over bite was reduced in one of the case and overjet was increased in both of the patients. For stabilization, corrected Class II unilateral molar relationship was maintained with Nance button for 2 months. At the end of the fixed orthodontic treatment maxillary incisor proclination was reduced back to the original inclination. In conclusion this newly developed device achieved bodily distal molar movement with minimum patient cooperation.